Empowering Women as Agents of Change in reducing Stunting in Indonesia - Willya Achmad (SEAN Institute, 2024)
Stunting, which is a serious public health problem, has long-term impacts on children's growth and development. Women's empowerment is identified as a strategic key in overcoming the root causes of stunting, including limited access to nutrition, education and health services. Therefore, this research aims to explore the role of women's empowerment as agents of change in efforts to reduce stunting rates in Indonesia. This research uses a qualitative approach with descriptive methods. The research results confirm that women's empowerment has a crucial role in reducing stunting in Indonesia. Through education, women are empowered to provide optimal nutritional care and monitoring for children, while economic empowerment increases family access to nutritious food and reduces the risk of stunting. Empowered women also serve as agents of outreach and advocacy, raising awareness in communities and bringing about changes in societal norms and practices related to child care. Women's active participation in health and food programs, such as nutrition empowerment programs, strengthens their understanding of nutritional needs and strategies for overcoming the problem of stunting at the household level. Overall, women's empowerment not only has an impact on women themselves, but also brings positive changes to the welfare of families and society at large, supporting efforts to reduce stunting rates in Indonesia.